2002
DOI: 10.1614/0890-037x(2002)016[0224:iuoeaa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Use of Endothall and a Fungal Pathogen for Management of the Submersed Aquatic Macrophyte Hydrilla verticillata1

Abstract: Laboratory experiments were conducted in 55-L aquaria to evaluate the efficacy of the aquatic herbicide endothall and the fungal pathogen Mycoleptodiscus terrestris (Gerd.) Ostazeski, applied alone and in combination against hydrilla. Treatments included 0.25, 0.50, and 1.25 mg ae/L endothall, 100, 200, and 400 colony-forming units (CFU)/ml M. terrestris, simultaneous integrated treatments of 0.25, 0.50, and 1.25 endothall + 100 or 200 CFU/ml M. terrestris, sequential integrated treatments of 100 and 200 CFU/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 5 publications
0
22
0
3
Order By: Relevance
“…O hábito perene de crescimento, a profundidade de colonização, a facilidade de propagação por segmentos de plantas e o próprio ambiente aquático, levando à diluição de agentes de controle, são problemas a serem enfrentados. No entanto, o hábito perene e a formação de grandes colonizações as tornam alvos ideais para a adoção de medidas de controle biológico (Shearer, 1996). Este mesmo autor destaca o controle biológico como a medida mais viável para esse tipo de vegetação.…”
Section: Introductionunclassified
“…O hábito perene de crescimento, a profundidade de colonização, a facilidade de propagação por segmentos de plantas e o próprio ambiente aquático, levando à diluição de agentes de controle, são problemas a serem enfrentados. No entanto, o hábito perene e a formação de grandes colonizações as tornam alvos ideais para a adoção de medidas de controle biológico (Shearer, 1996). Este mesmo autor destaca o controle biológico como a medida mais viável para esse tipo de vegetação.…”
Section: Introductionunclassified
“…Shearer and Nelson (2002) evaluated co-application of M. terrestris with the herbicide endothall to improve control of hydrilla (Hydrilla verticillata) and also to minimize injury to non-target vegetation. At high treatment levels, both the pathogen and the herbicide have been reported to cause disease or injury to other plants (Shearer and Nelson, 2002;Shearer and Jackson, 2006). When used together, however, greater than 90% control was achieved in mesocosm studies, even with reduced rates of endothall and M. terrestris.…”
Section: Compatibility Of Bioherbicides With Other Management Practicesmentioning
confidence: 99%
“…When used together, however, greater than 90% control was achieved in mesocosm studies, even with reduced rates of endothall and M. terrestris. Non-target plant injury still occurred, but the researchers suggested that this integrated control offered a means of effective hydrilla control while altering the dosage of bioherbicide and chemical herbicide to protect desirable vegetation (Shearer and Nelson, 2002).…”
Section: Compatibility Of Bioherbicides With Other Management Practicesmentioning
confidence: 99%
“…Within 8 days, hydrilla tissues were completely colonized by the pathogen. Subsequent hydrilla collections in Texas resulted in the isolation of a very aggressive strain of M. terrestris that demonstrated excellent potential for hydrilla control alone or in combination with chemical herbicides (Netherland and Shearer 1996;Shearer 1997Shearer , 1998Nelson, Shearer, and Netherland 1998;Shearer and Nelson 2002).…”
Section: Introductionmentioning
confidence: 99%